The Current Perspectives and Piano Accompaniment of Guangdong Opera - Li, Song; Hiranrak, Sakchai (Journal of Roi Kaensarn Academi, 2024)
The Guangdong Opera is a significant musical composition that emphasises the importance of piano accompaniment in Chinese opera. This article aims to explain that the accompanist's role is to provide piano accompaniment that supports and validates the vocal rendition, elevating the vocalist's voice for close companionship and conversation. The Guangdong Opera is a traditional Chinese art form that emphasises the importance in Chinese opera. This article aims to explain that the role of accompanist in Cantonese opera vocal singing is to provide piano accompaniment, imitate the accompaniment of the band, support and assist vocal performance, and improve the singer's voice to achieve a tacit understanding. A study suggests that computer-generated accompanists should adjust their performance to match that of a soloist, but it is crucial for the two musicians to collaborate in shaping the performance. Accompanists in educational institutions must possess specific expertise and competencies related to performing arts, such as breath control, resonance cavity, articulation, and respiration. The design and implementation of a piano-assisted automated accompaniment system can regulate the acoustic quality of a pianist performing opera, ensuring high-quality performances.